Design of a Wearable Walking Aid Based on Anthropometric Measurement of Cerebral Palsy Children in Malaysia - Anuar, Adzly; Mahamud, Farid; Md Saad, Juniza; Rana Singam, Kesavan (2018 3rd International Conference on Control, Robotics and Cybernetics (CRC), 2018)
Children suffering from cerebral palsy (CP) tend to have difficulties in moving around, as the condition would affect their walking gait posture. A suitable walking aid would help CP children to maintain balance and body posture during standing and walking. Due to their condition, CP children often have different anthropometric measurement or body sizes compared to children without disabilities. This is one of the biggest challenges as designing assistive devices such as the walking aid, would require suitable dimensions, otherwise it would not fit and cause discomfort, or might further deteriorate the condition of the CP child. This paper describes the work done to acquire anthropometric measurement from CP children in Malaysia and utilizing these measurements in designing the wearable walking aid.